The effects of chlorination and epoxidation on mooney viscosity, curing characteristics and vulcanisate properties of silica filled chlorinated epoxidised natural rubber - Thitithammawong A; Kasoe R; Nakason C (Journal of Rubber Research, 2015)
Chlorinated epoxidised natural rubber (CENR) was compared to natural rubber (NR) and epoxidised natural rubber (ENR) in terms of compound and vulcanisate properties. Replacing double bonds in isoprene units by epoxidised groups and addition of chlorines affect regularity of the NR molecules. Reduction in the active unsaturated sites that can react with soluble sulphurating agent, the alteration of regularity relative to NR, together with the strong interchain interactions occurred between polar functional groups and their interactions with silica increase Mooney viscosity and decrease curing rates of ENR and CENR. They also have significant effects on mechanical, dynamic rheological and thermal properties as well as flammability of the rubber vulcanisates. THe CENR has slightly inferior mechanical and dynamic rheological properties but superior thermal stability and flammability, in comparison to ENR and NR.
Source Year: 2015
Keywords: Chlorinated epoxidised natural rubber; Composite; Modification; Silica; Vulcanisate properties